THE EFFECT OF INCOME DIVERSIFICATION STRATEGY ON CREDIT RISK AND MARKET RISK IN COMMERCIAL BANKS IN INDONESIA DURING THE COVID-19 PANDEMIC - Otto Fitriandy; Irene Rini Demi Pangestuti (RADJA PUBLIKA, 2025)
The phenomenon of economic instability due to the COVID-19 pandemic has encouraged banks to improve income diversification strategies in order to reduce risk exposure and maintain sustainable financial performance. This study aims to analyze the effect of income diversification on credit risk and market risk with the role of control variables Size, Tangible Asset, Return on Asset and Liquidity. The study was conducted at Conventional Commercial Banks in Indonesia during the period 2018-2023. This research method uses a quantitative approach with secondary data. The population in this study is all Conventional Commercial Banks in Indonesia as many as 105 banks, then the sample determination uses purposive sampling technique and produces 101 banks as samples. The observation period for six years produced a total of 606 observation data. The analysis tool uses SPSS 26.0 software through multiple regression tests. The first regression results show that income diversification has a significant negative effect on credit risk (sig. 0.000; t-stat -3.170). Meanwhile, the size control variable does not affect credit risk (sig. 0.353; t-stat 0.930), Tangible does not affect credit risk (sig. 0.261; t-stat -1.125). ROA has a positive effect on credit risk (sig. 0.000; t-stat 6.399). Liquidity has a positive effect on credit risk (sig. 0.000; t-stat 6.355). The R² value of 0.204 indicates that 20.4% of the variation in credit risk can be explained by income diversification, and the control variables Size, Tangible Asset, Return on Asset and Liquidity. In the second regression, income diversification has a significant negative effect on market risk (sig. 0.049; t-stat -1.972). Meanwhile, the control variable size has a positive effect on market risk (sig. 0.002; t-stat 3.049), Tangible has no effect on market risk (sig. 0.493; t-stat -0.686). ROA has a negative effect on market risk (sig. 0.002; t-stat 3.184). Liquidity has a positive effect on market risk (sig. 0.000; t-stat 21.080). The R² value of 0.583 indicates that 58.3% of the variation in market risk can be explained by income diversification, and the control variables Size, Tangible Asset, Return on Asset and Liquidity.